Investigating Female Shoppers’ Attitude and Purchase Intention toward Green Cosmetics in South Africa - Shimul, Anwar Sadat; Cheah, Isaac; Khan, Basheera Bibi (Taylor & Francis, 2022)
This paper investigates female shoppers’ attitude and purchase intention toward green cosmetics. Underpinned with an extended theory of planned behavior model, the research framework examines consumers’ attitude and purchase intention. In addition, the moderating influence of consumer involvement is tested. Data (n = 408) were collected from South Africa and analyzed through structural equation modeling. The results show that subjective norm has a significant positive impact on the consumers’ purchase intention for green cosmetics. Also, ecological motive and environmental knowledge impact the consumers’ attitude toward green cosmetics. In addition, consumers’ involvement strengthens the positive relationship between attitude and purchase intention. However, the role of perceived behavioral control and health consciousness were non-significant. The findings suggest that practitioners should try to enhance the consumers’ knowledge and involvement about green cosmetics. They should inform and educate the consumers through an integrated marketing communication approach by means of campaigns, advertisements, and public relations. Thus, through relevant environmental information or knowledge, consumers will be more educated aiming to impact positive attitude and purchase intention.